Propuesta de producción de bioabono a partir de estiércol bovino en la finca El Valle, Subachoque, Cundinamarca (2019)
In this project a proposal was proposed to improve the process of transformation of the organic waste generated in the milking system of the El Valle farm, implementing an anaerobic fermentation system based on the use of built bioreactors and the evaluation of parameters and characteristics of organic materials and the resulting fertilizers.